Myrtle (Myrtus communis) essential oil effect on in vitro ruminal fermentation of a diet based on ray-grass and concentrate - Bettaieb A.; Darej C.; Moujahed N. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The aim of the current study was to evaluate the effect of Myrtus communis essential oil (EO) on in vitro rumen fermentation of a diet based on ray-grass and concentrate. Myrtle leaves and twigs were collected from the Eastern Region of Tunisia (Zaghouan) in spring. The EO was extracted using hydro-distillation and analyzed using GC/MS. Increasing doses of EO (0 ; 5 ; 10 ; 20 ; 40 ; 80 ; 120 μL/0.5 g of substrate) were added to a ration composed of ray-grass hay and concentrate (50/50% on DM basis) and incubated in glass syringes using rumen content from sheep as inoculum simulating rumen conditions and then fermentation parameters were measured. Tow syringes were reserved to determine true organic matter degradability (TOMD). Short chain fatty acid concentration (SC-FA) and partitioning factor (PF) were calculated. GC/MS results showed that the main components of myrtle EO were α-pinene (29.5%), limonene (20.4%) and linalool (11.5%). After 24 h of fermentation, gas production (GP) decreased significantly (P<0.0001) from 10 to 120 μL doses (i.e. 93.4, 84.3, 70.3, 35.3 and 25.3 ml, respectively for 10, 20, 40, 80 and 120 μL). For all these EO doses, GP values were different (P<0.0001). The same trend (P<0.0001) was observed for calculated SC-FA concentrations. Concerning TOMD, no significant differences were noted between 0, 5 and 10 μL doses (averaged: 60.3%), but values decreased significantly (P<0.0001) for 20, 40, 80 and 120 μL (i.e. 54.9%, 49.8%, 45.9%, and 44.0% respectively). Partitioning factor values were equivalent for 0, 5 and 10μL of EO (Averaged: 6.61), but the observed values increased significantly (P<0.0001) for 20μL (7.12), 40μL (7.85), 80 μL (14.06) and 120 μL (18.51). It was concluded that myrtle EO can be envisaged as a potential additive to manipulate rumen fermentation and improve feed efficiency in ruminant.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)